Influenza virus surveillance in Argentina during the 2012 season: Antigenic characterization, genetic analysis and antiviral susceptibility - Benedetti, Estefanía (2016)
The activity and circulation of influenza viruses in Argentina was studied during 2012 as part of the Argentinean Surveillance for Influenza and other Respiratory Viruses, in the context of Global Influenza Surveillance. The antigenicity and molecular characteristics of haemagglutinins (HA) of circulating influenza A and B viruses were analysed to assess the emergence of virus variants. Susceptibility to oseltamivir and zanamivir was evaluated by enzymatic assay and results were backed-up by sequencing of the neuraminidase (NA) genes. During the 2012 season, influenza virus circulation in Argentina was detected from weeks 24 to 51. The HA sequences of the studied A(H1N1)pdm09 subtype viruses segregated in a different genetic group compared to those identified during the 2009 pandemic, although they were still closely related antigenically to the vaccine virus A/California/07/2009. The HA sequences of the A(H3N2) viruses analysed fell into the A/Victoria/208/2009 clade, genetic group 3C. A mixed circulation of virus variants belonging to B/Victoria and B/Yamagata lineages was detected, with B/Victoria being dominant. All viruses tested were sensitive to oseltamivir and zanamivir except one. This isolate, an A(H1N1)pdm09 virus possessing the substitution NA-N295S, showed highly reduced inhibition by oseltamivir and reduced inhibition by zanamivir. Virological and epidemiological surveillance remains critical for detection of evolving influenza viruses.